Women's entrepreneurial competence within a patriarchal social system - Hilmiana Hilmiana; Devi Alviani (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2023)
Women in patriarchal social systems face various challenges that affect their economic access and hinder their empowerment. This research aims to identify the competencies required by women to thrive within a patriarchal social system, reduce gender disparities, and promote empowerment in various aspects of life. This research utilized secondary data from the Scopus database and applied a document study method. Keywords used for the search included